PENERAPAN MODEL PEMBELAJARAN DIRECT IINSTRUCTION (DI) TERHADAP PRESTASI BELAJAR MAHASISWA PRODI PENDIDIKAN TIK IKIP PGRI PONTIANAK - Utin Susiaty (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2017)
The aims of this study were to investigate the improvement of student achievement after given DI model. This research used quasi experimental research. The data collection technique was include test methods for data for student achievement. The data was analyzed using n-gain analyzed (before-after analyzed). Based on these results it can be concluded there is improvement of student achievement after given DI model. The result of the normalized gain score analysis obtained 2 students (6.25%) got high gain score, 14 students (43,75%) got medium gain score and 16 student (50%) got low gain score and overall average gain score students of 0.26 are categorized as low.